دراسة السمية الحادة للمبيد الحشري كلوربيريفوس Chlorpyrifos على ثلاثة أنواع من متفرعات القرون Cladocerans - سابا, ميشيل (Latakia University Journal -Biological Sciences Series, 2016)
تمت مقارنة الحساسية السمية الحادة لثلاثة أنواع من متفرعات القرونDaphnia magna و Ceriodaphnia quadrangular و Moina rectirostris اتجاه المبيد الحشري Chlorpyrifos . وكانت النتائج كالتالي : النوع Ceriodaphnia quadrangular هو الأكثر حساسية للمبيد الحشري Chlorpyrifos يليه النوع Moina rectirostris وهما متقاربان إلى حد ما ، بينما النوع Daphnia magna كان الأقل حساسية لهذا المبيد . بين تقييم درجة السمية اعتماداً على الوحدات السميةTU للمبيد على حيوانات التجربة أنه ذو سمية عالية جداً من المستوى الخامس للنوعين Ceriodaphnia quadrangular و Moina rectirostris أما بالنسبة للنوع Daphnia magna فهو من المستوى الرابع / عالي السمية/. كل زيادة في تركيز المبيد واحد ميكروغرام بالتر تزيد معدل النفوق في أفراد جماعة النوع المدروس حوالي : Daphnia magna 68% و Ceriodaphnia quadrangular 334% و Moina rectirostris 277% يمكن أن يلعب قد الحيوان دوراً في حساسيته اتجاه المواد الكيميائية السامة ، وكلما كبر قد الكائن ازدادت قدرته على التحمل وقلت حساسيته . إن نفوق العوالق الحيوانية المدروسة وانخفاض غزارتها في موقعها الحيوي يسبب اضطرابات في التأثيرات المتبادلة بين مكونات المجتمع الحيوي في النظام البيئي المائي . نوصي باستخدام جماعة Ceriodaphnia quadrangular كحيوانات تجربة لتحديد سمية المواد الكيميائية السامة كونها أكثر حساسية . Two cladocerans species, Ceriodaphnia quadrangular, Moina rectirostris, were compared with Daphnia magna for their acute sensitivity to Chlorpyrifos insecticide . • The species Ceriodaphnia quadrangular is the most sensitive to the Insecticide Chlorpyrifos followed by Moina rectirostris. Both of them are close to some extent, while Daphnia magna was less sensitive to this pesticide. Ceriodaphnia quadrangular was more sensitive than Daphnia magna by up to a factor of 27. •The assessment of the degree of toxicity of the pesticide on the experimental animals shows that it is highly toxic of the fifth level of both species Ceriodaphnia quadrangular and Moina rectirostris . As for the Daphnia magna, it is of the fourth level / high toxicity/. • Each increase in the concentration of the pesticide 1.0µg/L leads to increase in the mortality rate of the Cladocerans studied: Daphnia magna 68% - Ceriodaphnia quadrangular 334% - Moina rectirostris 277%. • the bigger the animal, the less it was sensitive to toxic chemicals. • The death of planktons and their few numbers in the bio-community cause disturbances in the interactions between the components of this bio-community in the aquatic ecosystem. • We recommend using Ceriodaphnia quadrangular as experimental animals to determine the toxicity of toxic chemicals because of their high sensitivity .